Cerebral Erythropoietin Prevents Sex-Dependent Disruption of Respiratory Control Induced by Early Life Stress - Elliot-Portal, Elizabeth; Arias-Reyes, Christian; Laouafa, Sofien; Tam, Rose; Kinkead, Richard; Soliz, Jorge (Frontiers in Physiology, 2021)
Injuries that occur early in life are often at the root of adult illness. Neonatal maternal separation (NMS) is a form of early life stress that has persistent and sex-specific effects on the development of neural networks, including those that regulate breathing. The release of stress hormones during a critical period of development contributes to the deleterious consequences of NMS, but the role of increased corticosterone (CORT) in NMS-induced respiratory disturbance is unknown. Because erythropoietin (EPO) is a potent neuroprotectant that prevents conditions associated with hyperactivation of the stress neuroaxis in a sex-specific manner, we hypothesized that EPO reduces the sex-specific alteration of respiratory regulation induced by NMS in adult mice. Animals were either raised under standard conditions (controls) or exposed to NMS 3 h/day from postnatal days 3–12. We tested the efficacy of EPO in preventing the effects of NMS by comparing wild-type mice with transgenic mice that overexpress EPO only in the brain (Tg21). In 7-days-old pups, NMS augmented CORT levels 2.5-fold by comparison with controls but only in males; this response was reduced in Tg21 mice. Respiratory function was assessed using whole-body plethysmography. Apneas were detected during sleep; the responsiveness to stimuli was measured by exposing mice to hypoxia (10% O2; 15 min) and hypercapnia (5% CO2; 10 min). In wild-type, NMS increased the number of apneas and the hypercapnic ventilatory response (HcVR) only in males; with no effect on Tg21. In wild-type males, the incidence of apneas was positively correlated with HcVR and inversely related to the tachypneic response to hypoxia. We conclude that neural EPO reduces early life stress-induced respiratory disturbances observed in males.